2000
DOI: 10.1590/s0101-81752000000400013
|View full text |Cite
|
Sign up to set email alerts
|

Subulura lacertilia sp.n. (Nematoda, Subuluridae) parasitizing the Brazilian lizard Tropidurus nanuzae Rodrigues (Lacertilia, Tropiduridae)

Abstract: ABSTRACT. This report deals with the identification of samples of nematodes recovered from TI"opiduI"us nanuzae Rodrigues, 1981 , with the description of a new species, and is a part of a maj or study on helminth parasites of reptiles in Brazil, taking into account previous data on thi s subject. The main approach is that refen·ing to the first occurrence of subulurid nematodes in a reptilian host, since they have been assigned previously to birds and mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Physalopteroides venancioi has been previously found infecting the lizards Ameiva ameiva (Vrcibradic et al, 2000b), Tropidurus torquatus (Vrcibradic et al, 2000a), Mabuya macrorhyncha and M. agilis (Vrcibradic et al, 2000a(Vrcibradic et al, , 2002b and the toad Bufo paracnemis (Lent et al, 1946). Subulura lacertilia, a recently discovered and described species, was previously known only from the iguanian Eurolophosaurus nanuzae (formerly in the genus Tropidurus; see Frost et al, 2001) from a montane region in central Minas Gerais State, Brazil (Vicente, et al, 2000); the present record thus represents the second host reported for S. lacertilia, as well as an extension of its distribution to coastal Brazil. Skjrabinelazia intermedia was previously known only from lizards of the genus Tropidurus (Vicente et al, 1993;Vrcibradic et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Physalopteroides venancioi has been previously found infecting the lizards Ameiva ameiva (Vrcibradic et al, 2000b), Tropidurus torquatus (Vrcibradic et al, 2000a), Mabuya macrorhyncha and M. agilis (Vrcibradic et al, 2000a(Vrcibradic et al, , 2002b and the toad Bufo paracnemis (Lent et al, 1946). Subulura lacertilia, a recently discovered and described species, was previously known only from the iguanian Eurolophosaurus nanuzae (formerly in the genus Tropidurus; see Frost et al, 2001) from a montane region in central Minas Gerais State, Brazil (Vicente, et al, 2000); the present record thus represents the second host reported for S. lacertilia, as well as an extension of its distribution to coastal Brazil. Skjrabinelazia intermedia was previously known only from lizards of the genus Tropidurus (Vicente et al, 1993;Vrcibradic et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…the genus Subulura Molin, 1860 currently includes over 70 nominal species, many of which were considered as species incertae sedis by inglis (1958) because of the poorly known information on the structure of the head. the adults of Subulura are frequently found in the digestive tract of birds and mammals, and can also occur in lizards (Barreto 1918, cram 1927, ilyas 1982, Diouf et al 1998, Vicente et al 2000, Ubelaker et al 2007, Ming and Zhang 2010. Based on the cephalic structures, especially the presence or absence of labial lobes and interlabia surrounding the oral aperture, Subulura falls into three subgenera, Subulura Molin, 1860, Murisubulara Quentin, 1969and Tepuinema Díaz-Ungía, 1964, according to chabaud (1978.…”
Section: Redescription Of Subulura Hallimentioning
confidence: 99%
“…Subulurids are transmitted by arthropod intermediate hosts [Anderson, 1988] and typically have a wide host range, including mammals, birds and reptiles [Vicente et al, 2000]. These parasites reside in the large intestines and caeca of their hosts [Baker, 2007] and although they can cause intestinal perforation [de Melo, 2004], they are not known to be highly pathogenic [Petrzelkova et al, 2006].…”
Section: Parasites Transmitted Via An Intermediate Hostmentioning
confidence: 99%